USING SPECIAL ECONOMIC KNOWLEDGE TO COLLECT EVIDENCE OF FINANCIAL OFFENSES (Law and Safety, 2018)
The author has proved the need for the involvement of economists to collect evidence of the commission of financial offenses.It has been noted that since the main sources of evidence of committing offenses in the financial sphere are information from primary accounting documents, accounting registers, financial and tax reporting, then there is a number of issues related to the collection and evaluation of evidence of offenses in the financial sector. It has been emphasized that the rules of the admissible proof take the special place in the assessment of proving; the author has provided the conditions for the admissibility of the evidence.The author states that the main types of evidence for the detection and investigation of financial offenses are documents, including the findings of audits and acts of financial control inspections with all appendices (primary accounting documents, accounting registers, etc.). In such circumstances, an expert in the field of economy must address a wide range of issues that belong to different areas of financial and economic knowledge. Therefore, he must have knowledge and skills in all the general theoretical economic disciplines to the extent necessary to accurately assess the eligibility of financing, lending, tax and accounting, internal control, financial, tax and statistical reporting of various business entities. The author has specified the requirements for a person being invited as a specialist; and has determined the rights and obligations assigned to the specialist during the execution of procedural actions.The author has characterized the cases of the need to involve a specialist in the sphere of economy to participate in investigative and judicial actions, namely: to detect, review and collect documents that will be used as evidence; to solve the issue of reference character in the finance field; to review accounting documents and registers that are already in the law enforcement agencies; to establish the value of the seized financial and accounting documents or their certain parts; cases when with the help of a specialist it is possible to collect materials for conducting forensic and economic examination, etc.
Keywords: financial offenses, inspections, evidence, special economic knowledge, specialists in the sphere of economy, qualification, rights and duties of specialists.